2017
DOI: 10.3892/mmr.2017.7411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anticholinergic agent on miRNA profiles and transcriptomes in a murine model of allergic rhinitis

Abstract: Anticholinergic agent, ipratropium bromide (IB) ameliorates symptoms of allergic rhinitis (AR) using neuroimmunologic mechanisms. However, the underlying molecular mechanism remains largely unclear. In the present study, 27 mice with AR induced by ovalbumin were randomly allocated to one of three groups: Model group, model group with IB treatment for 2 weeks, and model group with IB treatment for 4 weeks. Allergic symptoms were evaluated according to symptoms scores. Differentially expressed genes [microRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…In our previous studies, nasal vidian neurectomy achieved a good therapeutic effect in patients with refractory AR, and IB has been shown to reverse the nasal mucosal Th2 advantage in BALB/c mice. 6,14,15 Similar to our previous studies, in the present in-vitro neuroimmune coculture study, D-U87 neurons promoted the polarization of CD4 + T cells from patients with AR toward Th2 cells, and the increased percentage of Th2 cells was then reduced by IB treatment. Interestingly, in contrast to observations in cells from patients with AR, CD4 + T cells from healthy controls polarized into Th1 cells after coculture with D-U87 neurons.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our previous studies, nasal vidian neurectomy achieved a good therapeutic effect in patients with refractory AR, and IB has been shown to reverse the nasal mucosal Th2 advantage in BALB/c mice. 6,14,15 Similar to our previous studies, in the present in-vitro neuroimmune coculture study, D-U87 neurons promoted the polarization of CD4 + T cells from patients with AR toward Th2 cells, and the increased percentage of Th2 cells was then reduced by IB treatment. Interestingly, in contrast to observations in cells from patients with AR, CD4 + T cells from healthy controls polarized into Th1 cells after coculture with D-U87 neurons.…”
Section: Discussionsupporting
confidence: 88%
“…Most clinical investigations and animal studies have revealed an important role for nerves in AR , ; however, controversy exists regarding whether parasympathetic nerves exert an effect on immune regulation. In our previous studies, nasal vidian neurectomy achieved a good therapeutic effect in patients with refractory AR, and IB has been shown to reverse the nasal mucosal Th2 advantage in BALB/c mice , , . Similar to our previous studies, in the present in‐vitro neuroimmune coculture study, D‐U87 neurons promoted the polarization of CD4 + T cells from patients with AR toward Th2 cells, and the increased percentage of Th2 cells was then reduced by IB treatment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[57] Nasal glucocorticoids is currently the most effective drugs for the treatment of AR, for patients with bronchial asthma, can be conducive to asthma control and improve lung function. [8,9] Other drugs, including antihistamines, [10] antileukotrienes, [11] mast cell membrane stabilizers, [12] decongestants, [13] and anticholinergics, [14] are also commonly used. Allergen-specific immunotherapy has short-term and long-term effects on AR, preventing the development of asthma and reducing new sensitization.…”
Section: Introductionmentioning
confidence: 99%